2011
DOI: 10.3892/or.2011.1139
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of gemcitabine sensitivity in pancreatic cancer by co-regulation of dCK and p8 expression

Abstract: Abstract. The purpose of this study was to improve the gemcitabine sensitivity in pancreatic cancer by adenovirusmediated co-regulation of dCK and p8 expression. Firstly, we analyzed the sensitivity of three human pancreatic tumor cell lines (Capan-2, Panc-1 and BxPc-3) to gemcitabine using MTT assays, and found Panc-1 to be relatively resistant to gemcitabine. Further, we investigated the expression of dCK and p8 in different pancreatic cancer cell lines using real-time PCR and Western blot analysis, and foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…The obtained resistance of PDAC cell lines to gemcitabine suggests that dCK is often inactivated [37]. Knockdown of the dCK gene often leads to gemcitabine resistance [38], while overexpression of dCK can restore the chemosensitivity of gemcitabine in gemcitabine-resistant cell lines [39,40]. A large number of clinical studies have shown that the dCK expression level in pancreatic cancer tissue is a reliable prognostic indicator of PFS, so dCK may be the best biomarker of dFdC sensitivity for PC patients treated with gemcitabin [41,42].…”
Section: Gemcitabine Resistance Mechanismsmentioning
confidence: 99%
“…The obtained resistance of PDAC cell lines to gemcitabine suggests that dCK is often inactivated [37]. Knockdown of the dCK gene often leads to gemcitabine resistance [38], while overexpression of dCK can restore the chemosensitivity of gemcitabine in gemcitabine-resistant cell lines [39,40]. A large number of clinical studies have shown that the dCK expression level in pancreatic cancer tissue is a reliable prognostic indicator of PFS, so dCK may be the best biomarker of dFdC sensitivity for PC patients treated with gemcitabin [41,42].…”
Section: Gemcitabine Resistance Mechanismsmentioning
confidence: 99%
“…Indeed, NUPR1 has recently elicited significant attention due to its role in promoting cancer development and progression in pancreas [18,19]. NUPR1-dependent effects also mediate resistance to anticancer drugs [20,21,22]. Remarkably, we have previously shown that genetic inactivation of Nupr1 antagonizes the growth of pancreatic cancer [16,23], and other laboratories have also demonstrated that genetic inactivation of NUPR1 stops the growth of hepatocarcinoma [24], non-small lung cancer [25], cholangiocarcinoma [26], glioblastoma [27], multiple myeloma [28,29], and osteosarcoma [30], thereby supporting NUPR1 as a promising therapeutic target for the development of new therapies against cancers.…”
Section: The Intrinsically Disordered Stress Protein Nupr1 In Pdacmentioning
confidence: 99%
“…Overexpression of dCK was found to significantly enhance gemcitabine sensitivity in two of three pancreatic cancer cell lines [36]. Furthermore, simultaneous expression of dCK and p8 in a gemcitabine-resistant pancreatic cancer cell line, PANC-1, significantly decreased the cytotoxic IC 50 of gemcitabine and enhanced apoptosis and caspase-3 activity; tumor growth inhibition was also noticeably improved in nude mice [37]. Clinically, low immunohistochemical expression of dCK was correlated with both decreased overall survival as well as older age of patients, suggesting a role of age-related methylation in patients [38].…”
Section: Determinants Of Chemoresistance In the Gemcitabine Pathwaymentioning
confidence: 99%
“…Tumor volume was reduced dramatically and mouse survival prolonged significantly due to an increase in apoptosis and decrease in cellular proliferation [103]. Recently, it has also been found that the overexpression of dCK and knockdown of p8 with recombinant adenoviral vectors also significantly decreased gemcitabine resistance in PANC-1 cells and inhibited tumor growth with enhanced apoptosis and caspase-3 activity [37]. …”
Section: Approaches To Directly Modifying Determinants Of Gemcitabmentioning
confidence: 99%